1984
DOI: 10.1037/0096-3445.113.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the response after feedback training for changes in heart rate and sudomotor laterality.

Abstract: What is the relation between the ability to control visceral responding on a biofeedback task and the ability to report behaviors actually contributing to this performance? Subjects received biofeedback training for unidentified visceral responses and then gave written reports about what they had done to control the feedback displays. Independent judges were given these reports and, on the basis of knowledge about activities known to contribute to visceral activity, were asked to determine the visceral respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
(100 reference statements)
1
8
0
Order By: Relevance
“…At some point the verbal (consciousness) system, which monitors the other information-processing systems, should seek to code the new behavior program in terms of its own referents. This is exactly what Roberts et al (1984) have recently reported. Their subjects were trained either to control heart rate or to produce lateralized changes in skin conductance, but possible clues as to the nature of the task were specifically concealed.…”
Section: A Two-process Theorysupporting
confidence: 91%
See 2 more Smart Citations
“…At some point the verbal (consciousness) system, which monitors the other information-processing systems, should seek to code the new behavior program in terms of its own referents. This is exactly what Roberts et al (1984) have recently reported. Their subjects were trained either to control heart rate or to produce lateralized changes in skin conductance, but possible clues as to the nature of the task were specifically concealed.…”
Section: A Two-process Theorysupporting
confidence: 91%
“…First, there has been mounting criticism of the various methods used to measure subjects' ability to discriminate autonomic and other internal responses. These have been voiced particularly strongly by Roberts on theoretical grounds (Roberts, 1977;Roberts, Williams, Marlin, Farrell, & Imiolo, 1984) and by Katkin, (Katkin, Morell, Goldband, Bernstein, & Wise, 1982) and Ross and Brener (1981) on empirical grounds. The thrust of those criticisms is on the one hand that inability to perform on a discrimination task often simply reflects inadequacies in the task.…”
Section: ; Italics In Original)mentioning
confidence: 99%
See 1 more Smart Citation
“…We also assessed the basis of SP regulation by analyzing verbal reports that subjects gave of their SP control strategies. To ensure the validity of the verbal report data, we used a feedback procedure that allowed self-report to arise only from the subject's memory of behavioral events related to feedback, and not from other sources of self-report that may operate in a feedback situation (e.g., response bias induced by task instructions or spatial orientation of the feedback display; see Roberts et al 1984). We were particularly interested in a contrast of frontal and parietal areaspecific SP self-regulation.…”
Section: Apparatus and Physiological Recordingsmentioning
confidence: 99%
“…In line with this important differ-ence between peripheral and central physiological processes, subjects who learned to control their autonomic responses were able to report much more consistent strategies they used for self-control (Roberts et al, 1984) than subjects who learned to control their electroencephalogram (EEG) (Roberts et al, 1989). However, the method of direct verbal description of one's conscious strategies may be too coarse to grasp possibly fluent perception of brain activity.…”
Section: Introductionmentioning
confidence: 96%